Comparison of Nutritional Value between Broiler Feather Flour and Fermented Broiler Feather Flour - Nautus Stivano Dalle; Hendrikus Demon Tukan; Elisabeth Yulia Nugraha (JURNAL ILMIAH PETERNAKAN TERPADU, 2022)
The aim of this study was to acknowledge the change in the nutrient content of fermented feather flour use a mixture of yeast tape and yeast bread. Feather flour used is a waste broiler feather flour obtained from the Oesao Presidential Market, Kupang Regency. Trial method used was a direct methods and fermented result through proximate analysis would be compared with before fermented. The design used was complete randomized design with 2 treatments and 3 replications. The treatment tested were R0: Broiler feather flour without fermented and R1: fermented broiler feather flour used yeast tape and yeast bread. Variable observed were the change in nutrient content in form of dry matter, crude protein, crude fat, crude fiber and material extract without nitrogen feather meal after fermented. Statistical analysis showed significant result (P<0.05) on variables and fermented used yeast tape and yeast bread could increase crude protein and crude fat with could reduce content of crude fiber, carbohydrates and material extract without nitrogen feather meal. The conclusion of this study was yeast tape and yeast bread could increase the nutrients in feather flour that could be used as indgredients mixed diet.